1999
DOI: 10.1086/313180
|View full text |Cite
|
Sign up to set email alerts
|

TheSolar Maximum MissionAtlas of Gamma‐Ray Flares

Abstract: We present a compilation of data for all 258 gamma-ray Ñares detected above 300 keV by the Gamma Ray Spectrometer (GRS) aboard the Solar Maximum Mission satellite. This gamma-ray Ñare sample was collected during the period from 1980 February to 1989 November ; covering the latter half of the 21st solar sunspot cycle and the onset of the 22d solar sunspot cycle. We describe the SMM/GRS instrument, its in-orbit operation, and the principal data reduction methods used to derive the gamma-ray Ñare properties. Util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 27 publications
3
69
0
Order By: Relevance
“…Vestrand et al (1999) identified 258 flare events using Solar Maximum Mission observations. Among these, many are electron-dominated events with no clear signature of gamma-ray emissions (Rieger & Marschhauser 1990;Marschhauser et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Vestrand et al (1999) identified 258 flare events using Solar Maximum Mission observations. Among these, many are electron-dominated events with no clear signature of gamma-ray emissions (Rieger & Marschhauser 1990;Marschhauser et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The likelihood of observing a flare with gamma-ray emission can be estimated by using the long-term observations of the RHESSI 9 and the Gamma Ray Spectrometer (GRS) on SMM 30 . Flare occurrence with respect to time is used to predict the performance of GRIPS to account for the non-Poisson nature of flare events: an active region that produces one gamma-ray flare is likely to produce others as well.…”
Section: Long-duration Balloon Flights (Ldbfs)mentioning
confidence: 99%
“…However, a M2 soft X-ray flare is not typically a prolific source of 2.223 MeV line emission. In fact, the catalog of g-ray flares observed by the Solar Maximum Mission (SMM) collected by Vestrand et al [1999] shows that the fluence of the 2.223 MeV g-ray line for flares of class M5 or lower was very low. Therefore, the production of solar neutrons by soft X-ray flares of a low class (i.e., M2) may be considered small.…”
Section: Energy Spectrum Of Solar Flare Neutrons As a Function Of Thementioning
confidence: 99%